The design of an intelligent wireless sensor network for ubiquitous healthcare - Fariborzi, H.; Moghavvemi, M.; Mehrkanoon, S. (2007)
This paper proposes the architecture of a wireless sensor network for remote monitoring of biomedical signals from multiple patients in hospital setting. The system addresses the strict requirements of high-density and moderate-mobility scenarios such as energy-awareness, self-healing, low data delivery delay and transmission reliability. The network is based on IEEE 802.15.4 standard and emerging ZigBee technology for low power and low rate data transmission. An optimized source routing protocol has been presented to control the network traffic load and energy consumption of the battery-powered nodes and hence increase the average delivery rate and effective network lifetime. The preliminary prototypes acquire and transmit 2-lead ECG through the license-free 2.4 GHz band